QUANTIFICATION OF HEAVY METALS AND MINERALS IN SELECTED INDIAN MEDICINAL PLANTS USING ATOMIC ABSORPTION SPECTROPHOTOMETER - C.RATHANAVEL; P.THILLAI ARASU (International Journal of Pharma and Bio Sciences, 2013)
Medicinal plants form the basis of sophisticated traditional medicine system that has been in existence for thousands of years, which continue to provide mankind with new remedies. Herbal plants are consumed worldwide for the treatment of several diseases and such plants are the important source of raw material for pharmaceutical industries. As a micronutrient, heavy metal plays an essential role in proper functioning of vital organs in the human body. The main objective of the present study is to quantify the non-essential heavy metals like As, Cd, Cu, Hg and Pb and essential Minerals like Fe, Mg, Mn, Na & Zn in some selected medicinal plants using Atomic Absorption Spectrophotometer. The concentration levels (mg/l) of trace elements in selected medicinal plants were estimated by wet digestion method. The whole plant, tuber part, root , leaf, bark and seeds of 20 different medicinal plants such as Indigofera tinctoria, Oldenlandiaumbellata, Acalpa indica, Indigofera aspalathoids ,Eclipta alba etc., were used for the analysis purpose. The results were compared with the safety standards established by the World Health Organisation (WHO). The acceptance criteria levels in most of the medicinal plants were within the safe limits.